The Growth and Production Improvement of Soybean Plant (Glycine max L.) by Applying The Local Microorganisms of Fruit Waste in Palopo - Rahman Hairuddin (Agrotech Journal, 2020)
This study was aimed to find out the effective local microorganism of fruit wastes concentration on the growth and production of the soybean plants. This study was conducted in the trial land of Campus 2, Faculty of Agriculture, Cokroaminoto University, Palopo from September to December 2019. The method used in this study was the randomized block design with 5 treatments and 4 replications, therefore there were 20 experimental units. Each experimental unit comprised 2 plant units, therefore there were 40 plant samples on the given concentration of P0: Control, P1: 50 mL/L fruit waste local microorganism concentration, P2: 100 mL/L fruit waste local microorganism concentration, P3: 150 mL/L fruit waste local microorganism concentration, and P4: 200 mL/L fruit waste local microorganism concentration. The results showed that the local microorganism application on the soybean plants had no significant effects on the plant height, total of leaves, flowering period, and a total of pods. The local fruit waste microorganism with 100 mL concentration was capable of improving the plant height, total of leaves, flowering period, and a total of pods with the respective average of 31.9 cm, 51.6 leaves, 21,8 days, and 35 soybean pods